Aerosol‐Assisted Synthesis of Porous TiNxOy@C Nanocomposites. Issue 33 (6th July 2016) - Maurice, Vincent; Clavel, Guylhaine; Antonietti, Markus; Giordano, Cristina
Abstract: Porous TiN x O y ‐based particles were synthesized by an aerosol spray process. At first, the starting sol solution containing the metal precursor and the nitrogen source is sprayed to form an aerosol that is subsequently pyrolysed at different temperatures. The obtained dried particles are an amorphous coordination "polymer" rich in carbon and nitrogen. These "glassy" particles are finally thermally treated at 800 °C, promoting the crystallization of the particles and the release of a major part of the carbon. As the particles keep their original shape, carbon loss and density increase during the crystallization step and lead to the development of an accessible pore structure. The process was analyzed and extended to the synthesis of other metal nitrides, such as VN and W2 N, thereby showing its general validity for the production of functional nanocrystalline nitride ceramics with high porosity still occupying a relatively small volume, and otherwise not easily accessible. Abstract : Ceramics : Porous TiN x O y @C nanocomposites were prepared at relatively moderate temperature without the assistance of any template by coupling an aerosol process with the urea glass route. The relative specific surface area (up to 187 m 2 g −1 ) and porosity can be adjusted by changing the reaction conditions (see figure).